Effect of peer health education intervention on HIV/AIDS knowledge amongst in-school adolescents in secondary schools in Imo State, Nigeria - Chinelo Judith Ezelote; Nkechi Joy Osuoji; Adaku Joy Mbachu; Chikadibia Kizito Odinaka; Ogochukwu Mildred Okwuosa; Chinaemelum Juliet Oli; Chimburuoma Georgina Ignatius (BMC, 2024)
Abstract Background Peer education is an approach to health promotion in which community members are supported to promote health-enhancing change among their peers. The study assessed the effect of peer health education on HIV/AIDS knowledge amongst in-school adolescents in secondary schools in Imo State. Methods This was an intervention study carried out among 296 and 287 in-school adolescents aged 15 to 19 years attending Akwakuma Girls Secondary School and Federal Government Girls College Owerri Imo State respectively. The study was in three stages: before intervention, intervention, and after intervention. The impact of peer education was evaluated twelve weeks after intervention. Data were collected using semi-structured questionnaires. The study utilized a quasi-experimental study design. The chi-square test and McNemar's test were used to test the hypothesis with a significance level of p ≤ 0.05. Results The result from the study revealed that the majority (73%) of the respondents at Akwakuma Girls Secondary School (test group) had poor knowledge of HIV/AIDS mode of transmission and prevention at baseline. The overall good knowledge of respondents in the test group improved from 27 to 81% after the intervention. 36% of the respondents in the control group had good knowledge at baseline, the knowledge of 64% of them with poor knowledge at baseline were compared post-test to those in the test group who also had poor knowledge at baseline. The knowledge of only 27.7% of those in the control group increased post-test while the remaining 72.3% still had poor knowledge. The result of the inter-school comparison using Chi-square revealed that the p-value was statistically significant. Intra-school comparison using McNemar's test revealed a statistical significance for all questions in the test group, while none was positively significant in the control group. Conclusions Peer health education improved the knowledge of the students at Akwakuma Girls Secondary School which was very low at the baseline. The knowledge of the students in the control group with poor knowledge at baseline didn't increase post-study. Peer health education should be strengthened and expanded as one of the tools for behavior change among adolescents. There should be more focus on adolescents for HIV-targeted prevention.